2016
DOI: 10.1159/000444734
|View full text |Cite
|
Sign up to set email alerts
|

Practice Patterns for Prophylaxis and Treatment of Venous Thromboembolism in German Cancer Patients

Abstract: Background: Venous thromboembolism (VTE) is a serious threat for cancer patients. Guidelines recommend low-molecular-weight heparin (LMWH) for prophylaxis and treatment, but it is unknown to what extent specialists adhere to these recommendations. This survey assesses the current approach to patients with cancer-associated VTE in Germany. Materials and Methods: A questionnaire was sent out to members of the DGHO (Deutsche Gesellschaft für Hämatologie und Onkologie), the BNHO (Berufsverband Niedergelassener Häm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 39 publications
3
23
0
2
Order By: Relevance
“…A recent German study exploring physicians' preferences for anticoagulation in CAT suggested oncologists believed the requirement for a patient or carer to administer a LMWH was an important factor in reducing adherence to this drug. 25 Our data directly challenges this perception and supports the assertion that the views of patients should not only be considered, but actively sought out in planning therapies. 26 Moreover, rather than relying on intuition on which to base expectations of patient preferences, the evidence base should be given due consideration.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 70%
See 1 more Smart Citation
“…A recent German study exploring physicians' preferences for anticoagulation in CAT suggested oncologists believed the requirement for a patient or carer to administer a LMWH was an important factor in reducing adherence to this drug. 25 Our data directly challenges this perception and supports the assertion that the views of patients should not only be considered, but actively sought out in planning therapies. 26 Moreover, rather than relying on intuition on which to base expectations of patient preferences, the evidence base should be given due consideration.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 70%
“…Whilst poor compliance with VTE clinical guidelines is not a new phenomenon, the reasons are not fully understood. 24,25 Specific to CAT, and despite qualitative data to the contrary, there is an ongoing perception that LMWH is unacceptable or burdensome to patients. 16,26,27 Whilst it is important to offer patients a choice in their anticoagulation treatment, it must be with the caveat that such a choice is informed by data and that preferences for certain Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Although anticoagulation with LMWH for three to six months is the treatment of choice for cancer-associated VTE, up to half of these patients still receive VKA and overall adherence to LMWH over the course of treatment is poor in clinical practice [51][52][53]. Frequent barriers to the guideline concordant long-term use of LMWH are higher treatment costs, deviating preferences of treating physicians, and the burden of daily subcutaneous injections [54].…”
Section: Are Doacs a Therapeutic Option For This Patient?mentioning
confidence: 99%
“…Predictive biomarkers for VTE in ambulatory cancer patients have been proposed but, the utility of them in gynaecological patients has not been well investigated [28]. Recent data from the Vienna prospective study show that elevated levels of P-selectin are predictive of thrombosis, and elevated D-dimer in addition to prothrombin 1.2 fragments (F1 + 2) are associated with increased risk of VTE in patients receiving chemotherapy [29]. Moreover, a prospective study reported 2.7-fold increase in arterial thrombosis, and a 47-fold increase in the mortality rate from VTE in patient undergoing chemotherapy compared to the general population [15].…”
Section: Treatment-related Riskmentioning
confidence: 99%